DIGITAL WORKFLOW IN DENTAL PROSTHETICS: FROM VIRTUAL PLANNING TO RESTORATION COMPLETION - Ramos, José Victor dos Santos; Mendes, Danilo Cangussu; Marson, Fabiano Carlos; Araujo, Fabiano de Oliveira; Milani, Paulo Augusto Pires; Cordoni, Rogério; Pupo, Fabrício Palermo; Cavalheiro, Amanda Kerin Alves; Pupo, Yasmine Mendes (Seven Editora, 2026)
Before the current technological evolution, photographs were widely used to aid in obtaining study models, but over time, facial scanners began to be used for 3D model analysis. In addition, computed tomography revolutionized diagnosis by being widely used in computers for virtual planning. The aim of this study was to conduct an integrative review of the literature on digital workflow in dentistry, with an emphasis on the stages of intraoral and extraoral scanning, virtual planning, and manufacturing, discussing its challenges and limitations. The methodology was based on searches in the PubMed, Capes, Science Direct and Scopus databases, selecting 74 articles published between 2000 and 2025. The results detail the phases of the workflow: data acquisition via tomography and scanners; prosthesis design (CAD), including Digital Smile Design (DSD); and final production (CAM) by milling or 3D printing. Finishing techniques, such as makeup and sintering, which are fundamental for aesthetics and resistance, are also addressed. It is concluded that the digital workflow increases clinical effectiveness and predictability, although it requires specialized training to master the tools.